2022
DOI: 10.1111/ijpo.12958
|View full text |Cite
|
Sign up to set email alerts
|

Modified body mass index z‐scores in children in New York City during the COVID‐19 pandemic

Abstract: Abstarct Objectives Determine whether the negative impact of the COVID‐19 pandemic on weight gain trajectories among children attending well‐child visits in New York City persisted after the public health restrictions were reduced. Study Design Multicenter retrospective chart review study of 7150 children aged 3–19 years seen for well‐child care between 1 January 2018 and 4 December 2021 in the NYC Health and Hospitals system. Primary outcome was the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our results also indicate a signi cant rise in the number of children suffering from overweight and obesity (3%) during this period. Our ndings are consistent with recent studies that have shown an increase in the prevalence of overweight and obesity among children and adolescents ranged from 7-13% during quarantine (11)(12)(13)(14)(15). Differences in higher rates of overweight and obesity in other studies may be attributed to variations in the timeframes for measuring and comparing weight and height among participants, as well as differences in sample sizes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also indicate a signi cant rise in the number of children suffering from overweight and obesity (3%) during this period. Our ndings are consistent with recent studies that have shown an increase in the prevalence of overweight and obesity among children and adolescents ranged from 7-13% during quarantine (11)(12)(13)(14)(15). Differences in higher rates of overweight and obesity in other studies may be attributed to variations in the timeframes for measuring and comparing weight and height among participants, as well as differences in sample sizes.…”
Section: Discussionsupporting
confidence: 91%
“…We did not specifically look at longitudinal changes in BMI in the same cohort, although the observed BMI z -scores based on our data was not different in our study from prepandemic to pandemic years. In another study examining the changes in BMI z -score in pediatric patients in municipal hospitals across NYC, there was an increase in annual BMI z -score from 2018 to 2019 by 3.1% and from 2019 to 2020 by 34.3% in the general pediatric population [ 13 ] which helps lend suspicion that perhaps the observed increased hospitalizations of T2DM or new-onset T2DM may be due to weight changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers reported an increase of obesity risk factors and rates of obesity during lockdown and suggested that it may lead to metabolic decompensation, triggering the increase of T2DM [13][14][15][16]. Recent studies also found increased incidence and prevalence rates of presentation of T2DM [6,11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Outside of the FBT literature, there has been limited epidemiological investigation into the relationship between parent and child weight trajectories. During the COVID‐19 pandemic, excessive weight gain had been reported in both adult and pediatric populations 24–28 . Additionally, having children at home was a significant predictor of pandemic weight gain among adults 29 .…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, excessive weight gain had been reported in both adult and pediatric populations. [24][25][26][27][28] Additionally, having children at home was a significant predictor of pandemic weight gain among adults. 29 Elucidating the natural relationship between parent and child weight trajectories may facilitate the designing of appropriate large-scale public health weight reduction interventions.…”
mentioning
confidence: 99%